Iron-catalysed stereoselective NH transfer enables dynamic kinetic resolution of sulfoxides - Fang-Xu Fan; Hui Xu; Shi-Xiong Tang; Yanfeng Dang; Fei Wang (Nature Communications)
Abstract Transition metal-catalysed asymmetric nitrene transfer provides a powerful means to access various bioactive N-containing compounds as single enantiomers. However, enantioselective NH transfer that allows concise assembly of unprotected enantioenriched amines remains an enduring challenge. We report here an iron-catalysed stereoselective NH imidation of sulfoxide, which is integrated with photocatalytic racemisation of sulfoxide, enabling a dynamic kinetic resolution (DKR) strategy for direct and asymmetric synthesis of NH-sulfoximines. This approach is distinct from the existing methods by avoiding protecting group manipulations and/or the use of chiral substrates. Computational studies on the NH imidation reaction suggest the involvement of an iron-aminyl radical intermediate, and its reaction with sulfoxide proceeds through a synchronous nucleophilic addition of sulfoxide to nitrogen center and ligand-to-metal single electron transfer process to form the N–S bond. In addition, the stereoselectivity is primarily dictated by the difference in dispersion interactions of the transition states.